Magnetic resonance imaging-arthroscopy correlation for chondral pathology in commonly imaged joints: a narrative review - Ian Savage-Elliott; Andrew J. Hughes; Jairo Triana; Zachary I. Li; Michael J. Alaia; Erin F. Alaia (Elsevier, 2024)
Accurate preoperative assessment of chondral pathology is crucial for the diagnosis and subsequent management of articular cartilage defects. Magnetic resonance imaging (MRI) is the mainstay for articular cartilage evaluation, defect characterization, and long-term monitoring of surgical outcomes. In the absence of direct arthroscopic imaging, MRI serves as the most accurate modality for the assessment of cartilage defects. Recent studies have focused on the discrepancies in diagnostic findings, which may arise when comparing MRI and arthroscopic imaging. This review focuses on describing the differences between MRI and arthroscopic imaging findings in relation to cartilage injury. It also highlights the current understanding of normal cartilage histology, methods of cartilage defect evaluation, and expands on joint-specific considerations of the commonly imaged articulations.